Pengaruh Layanan Bimbingan Klasikal Teknik Reward untuk Meningkatkan Konsentrasi Belajar Siswa Kelas VIII SMP Negeri Y - Diva Atmaja; Slamat Fitriyadi; Abd. Basith (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to: 1) determine the concentration level of eighth grade students of SMP Negeri Y using classical guidance services with reward techniques; 2) describe the implementation of classical guidance services with reward techniques in improving student learning concentration; and 3) determine the effect of classical guidance services with reward techniques on improving the learning concentration of eighth grade students of SMP Negeri Y. This study uses a quantitative approach with a Pre-Experimental research design. The research population was all 64 eighth grade students of SMP Negeri Y, while the research sample consisted of 22 students selected using the Simple Random Sampling technique. The research instrument used a learning concentration questionnaire that had been adjusted to the research indicators. The data analysis technique used was descriptive analysis to describe the initial and final conditions of student learning concentration, as well as a Paired Sample T-test to determine the significance of the differences before and after the service was given. The results showed that the average student learning concentration before being given classical guidance services was 59.50, while after being given the service increased to 83.05. The results of the Paired Sample T-test showed a sig. The t-value (2-tailed) was 0.000 < 0.05, meaning H0 was rejected and Ha was accepted. These findings indicate that the classical guidance service with reward techniques has a significant positive effect on students' learning concentration. Therefore, it can be concluded that classical guidance services with reward techniques have proven effective in improving the learning concentration of eighth-grade students at SMP Negeri Y. The results of this study are expected to serve as a reference for guidance and counseling teachers in selecting appropriate service strategies to help students improve their learning focus. This study also emphasizes the importance of motivation-based approaches in educational settings.